Telaah Kritis Pemikiran Jasser Auda dalam Buku “Maqasid Al-Shariah as Philosophy of Islamic Law: A Systems Approach” - Muhammad Baiquni Syihab (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
Jasser Auda was a Muslim intellectual who was known as a contemporary maqashid figure. But what was interesting about Jasser Auda's contemporary maqashid was the existence of a principle that prioritizes sharia maqashid over Islamic legal theory. It was not the same as the classical maqashid initiated by Iman al-Ghazali which revealed the maqashid sharia of Islamic law that was being applied in life in his era. The method used in this study was library research, namely the analysis of Jasser Auda's thoughts in his book entitled: